Systematic Literature Review: Financial Performance: The Effect of Green Accounting on Firm Value - Erlangga, Bayu; Muhammad Al-Aziz Fitra Bunaya; Fika Astrianti; Rina Yuniarti (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the increasing demands for sustainability and environmental transparency, which encourage companies to integrate Green Accounting into their business strategies to increase corporate value. The objective of this research is to synthesize empirical findings related to the influence of Green Accounting on corporate value, considering the roles of financial performance, operational efficiency, public legitimacy, and technological adaptation. The method used is a systematic literature review of various relevant empirical studies from various industrial sectors in Indonesia. The results of the study indicate that Green Accounting generally has a positive effect on corporate value through increased efficiency, profitability, and strengthening investor confidence, although the impact is contextual and influenced by the characteristics of the industrial sector. Financial performance has been shown to act as a mediator that strengthens or weakens this relationship. The implications of this research emphasize that Green Accounting is not merely an environmental obligation, but rather a strategic instrument for creating sustainable corporate value amidst global economic uncertainty.